Metabolic network of the gut microbiota in inflammatory bowel disease - Kohei Sugihara; Nobuhiko Kamada (BMC, 2024)
Abstract Gut dysbiosis is closely linked to the pathogenesis of inflammatory bowel disease (IBD). Emerging studies highlight the relationship between host metabolism and the modulation of gut microbiota composition through regulating the luminal microenvironment. In IBD, various disease-associated factors contribute to the significant perturbation of host metabolism. Such disturbance catalyzes the selective proliferation of specific microbial populations, particularly pathobionts such as adherent invasive Escherichia coli and oral-derived bacteria. Pathobionts employ various strategies to adapt better to the disease-associated luminal environments. In addition to the host-microbe interaction, recent studies demonstrate that the metabolic network between commensal symbionts and pathobionts facilitates the expansion of pathobionts in the inflamed gut. Understanding the metabolic network among the host, commensal symbionts, and pathobionts provides new insights into the pathogenesis of IBD and novel avenues for treating IBD.